The impact of federal housing policy on housing demand and homeownership: Evidence from a quasi-experiment - Edward J. Pinto; Stephen D. Oliner; Morris A. Davis; Tobias Peter (American Enterprise Institute (AEI), 2019)
In this paper, the authors exploit the Federal Housing Administration's (FHA's) surprise 50 basis point cut to its annual mortgage insurance premium in January 2015 to study the impact of federal housing policy and interest rates on housing demand for a population of households likely to be influenced by changes to policy.
Keywords: A; 330; mortgage; Federal Housing Administration (FHA); AEI Center on Housing Markets and Finance; Housing Center: Research